Effects of self - control modeling on learning a timing task - Esmaeil Nasiri; Ahmad Farokhi; Fazlollah Bagherzadeh (University of Tehran, 2015)
The purpose of the present study was to examine the effects of self - control modeling , that is presenting moded to learner whenever they asked for it, on learning a timing task.Twenty four right handed subjects (12 males, 12 females, aged 19-20) voluntarily participated in the study and were assigned randomly to two groups of self - control and yoked.The task was pressing the keys number 1, 4, 5 and 8 on a sequential timing apparatus while keeping certain absolute timig. People in the self - control group received the model whenever they requested it, while subjects in the other group were yoked with self - control group. The experiment consisted of acquistion, retention and transfer phases and absolute timing error was used as dependent variable. Results of factorial ANOVA in acqistion phase showed that even through there were a significant decrement in two groups on absolute timing error (P<0.05), but there were no significant decrement in two groups on absolute timing error (P<0.05), but there were no significant difference between two groups in this changes (P>0.05).Results of retention test failed to show any significant difference between two groups (P>0.05). but in transfer test self - control group showed significantly less error than yoked (P<0.05). the results showed that benefitcial effects of self - control technique anc well generalized to modeling domain and make practice conditions more accordant with informational needs of learners.